Smash! : exploring the mysteries of the universe with the Large Hadron Collider - Latta, Sara L. (Graphic Universe, 2017)
Nick and Sophie, two cousins, visit CERN and learn about the Large Hadron Collider, hidden particles, forces, and dark matter.